2017
DOI: 10.21273/jashs04145-17
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and Linkage Mapping of Eastern Filbert Blight Disease Resistance in ‘Uebov’ Hazelnut

Abstract: Eastern filbert blight (EFB) is a serious fungal disease of european hazelnut (Corylus avellana) in North America. The causal agent is the pyrenomycete Anisogramma anomala, which is native in the eastern United States where it occasionally produces small cankers on the wild american hazelnut (C. americana). However, most commercial cultivars of european hazelnut are susceptible. Infection leads to perennial cankers, girdli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The one progeny segregating for resistance from 'Moscow #37' had an excess of susceptible seedlings. An excess of susceptible seedlings was reported in previous EFB resistance studies in hazelnut (Colburn et al, 2015;Bhattarai et al, 2017b). Lunde et al (2006) noted an excess of resistant seedlings in the offspring of 'Zimmerman' , and that even when SSR markers indicate that the resistance gene is present, small cankers occasionally develop.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The one progeny segregating for resistance from 'Moscow #37' had an excess of susceptible seedlings. An excess of susceptible seedlings was reported in previous EFB resistance studies in hazelnut (Colburn et al, 2015;Bhattarai et al, 2017b). Lunde et al (2006) noted an excess of resistant seedlings in the offspring of 'Zimmerman' , and that even when SSR markers indicate that the resistance gene is present, small cankers occasionally develop.…”
Section: Discussionmentioning
confidence: 73%
“…Previously studied resistance sources include OSU 408.040 from Minnesota, ‘Culpla’ from Spain, OSU 495.072 from southern Russia, and ‘Crvenje’ and ‘Uebov’ from Serbia. Resistance from all five of these sources was placed on linkage group 6 (LG6) in the ‘Gasaway’ resistance region ( Sathuvalli et al, 2012 ; Colburn et al, 2015 ; Bhattarai et al, 2017b ). On the other hand, resistance in ‘Ratoli’ from Spain, C. americana ‘Rush’ from Pennsylvania and interspecific hybrid ‘Yoder #5’ from Ohio was assigned to a region on LG7 ( Sathuvalli et al, 2011a ; Bhattarai et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…However, deviation from the expected 1:1 segregation ratio (resistance: susceptible) was seen in four progenies in this study. In several previous studies, segregation distortion for EFB response was observed for 'Culpla', 'Crvenje', Russian OSU 495.072 (Colburn et al, 2015), 'Uebov' (Bhattarai et al, 2017a), and 'Zimmerman' (Lunde et al, 2006). In some progenies, there is an excess of resistant seedlings; while in others, there is an excess of susceptible seedlings.…”
Section: Discussionmentioning
confidence: 87%
“…Additional sources of EFB resistance have been identified and assigned to LGs. Resistance in OSU 408.040 from Minnesota (Sathuvalli et al, 2012), OSU 495.072 from Russia, 'Culpla' from Spain, and 'Crvenje' and 'Uebov' from Serbia (Bhattarai et al, 2017a;Colburn et al, 2015) was assigned to LG6. Resistance in 'Ratoli' from Spain (Sathuvalli et al, 2011a), C. americana 'Rush', and interspecific hybrid 'Yoder #5' (Bhattarai et al, 2017b) was assigned to LG7.…”
mentioning
confidence: 99%
“…SSR markers have the distinguishing features of multi-allelic, co-dominant inheritance patterns, reproducibility, high polymorphism, locus specificity, and transferability to related species and genera [5]. At present, more than 700 SSR loci have been developed in Corylus [6][7][8][9][10][11][12][13], and have been widely used in population structure assessment [14][15][16], germplasm identification and genetic diversity analysis [17][18][19][20], linkage map construction [21][22][23][24], and molecular marker-assisted selection [25,26]. In our previous study, we identified some cultivars of Ping'ou hybrid hazelnut by using the EST-SSR markers we developed in a pistil transcriptome [27].…”
Section: Introductionmentioning
confidence: 99%